Breeding indigenous livestock at ILRI: Red Maasai sheep in Kenya - Okeyo Mwai, Ally (International Livestock Research Institute, 2011)
For the November 2011 'liveSTOCK Exchange' event at the International Livestock Research Institute (ILRI), Okeyo Mwai reflects on livestock genetics research work with the native red Maasai sheep breed in Kenya